A New UPLC Approach for the Simultaneous Quantitative Estimation of Four Compounds in a Cough Syrup Formulation - Turak, Fatma; Guzel, Remziye; Dinc, Erdal (OXFORD UNIV PRESS INC, 2016)
A new ultra-performance liquid chromatographic (UPLC) method was developed for the simultaneous estimation of potassium guaiacolsulfonate (PGS), guaifenesin (GUA), diphenhydramine HCl (DIP) and carbepentane citrate (CAR) in a commercial cough syrup. The chromatographic separation of four compounds PGS, GUA, DIP and CAR was performed on a BEH phenyl column (100 x 2.1 mm, 1.7 mu m i.d.) using a mobile phase consisting of acetonitrile and 0.1 MHCl (50 : 50, v/v). In addition, the optimized conditions of the chromatographic analysis were found with the flow rate of 0.38 mL/min, the column temperature of 30 degrees C and the injection volume of 1.2 mu L with the photodiode array detection of 220 nm. Calibration curves in the concentration ranges of 10-98 mu g/mL for PGS, 5-80 mu g/mL for GUA, 5-25 mu g/mL for DIP and CAR were computed by the regression of the analyte concentration on the chromatographic peak area. The newly developed UPLC method was validated by analyzing the quaternary mixtures of the related compounds, intraday and interday experiment and standard addition samples. After method validation, the proposed UPLC approach was successfully applied for the analysis of the commercial syrup formulation containing PGS, GUA, DIP and CAR compounds.
Keywords: TANDEM MASS-SPECTROMETRY; LIQUID-CHROMATOGRAPHY; HUMAN PLASMA; DIPHENHYDRAMINE HYDROCHLORIDE; PENTOXYVERINE CITRATE; HUMAN SERUM; GUAIFENESIN; HPLC; DEXTROMETHORPHAN; PHARMACEUTICALS; Biochemistry & Molecular Biology; Chemistry